Functionalized nanoparticles for vaccine delivery - Bakan, Seyma; Salva, Emine; Tonbul, Hayrettin (Elsevier, 2026)
Vaccines are one of the most effective and cost-efficient public health interventions for preventing diseases. Today, vaccine types range from live attenuated vaccines to DNA and mRNA-based vaccines. Each vaccine type has advantages and limitations in terms of its ability to stimulate the immune system, antigen stability, and method of administration. Due to limitations such as low stability, limited targeting ability, and weak immunogenicity, the desired effect is not always achieved, and modern vaccine types, in particular, have increased the need for more sensitive delivery systems. At this point, functionalized nanoparticles have been developed to enhance the efficacy of both traditional and new-generation vaccines. Nanoparticle-based vaccine delivery systems ensure that antigens are delivered safely and in a controlled manner to target cells, while also optimizing antigen stability and interaction with the immune system. The surface properties, size, biodegradability level, and functionalizability of these systems with functional groups are decisive factors in terms of immunogenicity and targeting. Functionalization enables more effective transport of vaccine components to cells, increased interaction with antigen-presenting cells (APCs), and the achievement of stronger immune responses, both cellular (T cell response) and humoral (B cell and antibody response). When considering the functionality of various nanoparticle structures, such as liposomes, lipid nanoparticles, polymeric nanoparticles, inorganic nanoparticles, virus-like particles, and exosomes as carrier systems, each structure has different advantages, limitations, and application examples in vaccine delivery. According to studies conducted with these carrier systems, functionalization strategies have achieved high success in processes such as controlled release of antigens, targeting the target tissue, intracellular transport, and stimulation of the immune system. It has been observed that functionalized nanoparticles have strong potential not only in infectious diseases but also in cancer immunotherapy and the treatment of other immunological diseases. In conclusion, functionalized nanoparticles are emerging as promising carrier systems in modern vaccine technologies and offer innovative platforms that provide greater efficacy than traditional carriers in modern vaccine designs. © 2026 Elsevier Inc. All rights reserved..
Keywords: Drug; Drug delivery system; Functionalization; Immune system; modern vaccine; Nano particles; Vaccine delivery